1997
DOI: 10.1074/jbc.272.26.16374
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression of Caveolin-1 in Oncogenically Transformed Cells Abrogates Anchorage-independent Growth

Abstract: Caveolae are plasma membrane-attached vesicular organelles. Caveolin-1, a 21-24-kDa integral membrane protein, is a principal component of caveolae membranes in vivo. Both caveolae and caveolin are most abundantly expressed in terminally differentiated cells: adipocytes, endothelial cells, and muscle cells. Conversely, caveolin-1 mRNA and protein expression are lost or reduced during cell transformation by activated oncogenes such as v-abl and H-ras (G12V); caveolae are absent from these cell lines. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
336
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(365 citation statements)
references
References 81 publications
25
336
0
1
Order By: Relevance
“…Signi®cantly, heterologous expression of CAVEOLIN-1 has been shown to suppress ras and v-abl mediated oncogenic transformation of NIH3T3 ®broblasts (Engelman et al, 1997), and independently the anchorage-independent growth of mammary carcinoma-derived cell lines (Lee et al, 1998). We have mapped CAVEOLIN-1 to human chromosome 7q31.1, as a candidate for a multi-tissue tumour suppressor gene that has been localized to this subchromosomal region .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signi®cantly, heterologous expression of CAVEOLIN-1 has been shown to suppress ras and v-abl mediated oncogenic transformation of NIH3T3 ®broblasts (Engelman et al, 1997), and independently the anchorage-independent growth of mammary carcinoma-derived cell lines (Lee et al, 1998). We have mapped CAVEOLIN-1 to human chromosome 7q31.1, as a candidate for a multi-tissue tumour suppressor gene that has been localized to this subchromosomal region .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the extent of reduction in the expression of caveolin correlated with the ability of these oncogenically transformed cells to form colonies in soft-agar (Koleske et al, 1995). Induced expression of caveolin-1 in ras-transformed NIH3T3 cells was shown to abrogate anchorage-independent growth; this was accompanied by inhibition of the ras/raf/MAPK signalling pathway, and by induction of apoptosis (Engelman et al, 1997). Ectopic expression of Caveolin-1 in human breast tumour-derived cell lines has also been shown to suppress in vitro tumour growth (Lee et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…18 Since caveolin-1 acts as a negative regulator of signaling proteins in some normal cell types, 24 its re-expression on ovarian cancer cells might be partially responsible for restoration of growth control. Caveolin-1 re-expression might also be responsible for the acquired anchorage-dependent growth in NIH 3T3 cells 25 and in caveolin-1-transfected IGROV1 cells. 18 Cells with downmodulated FR expression exhibited a significant increase in a6b4 integrin expression and a drastic decrease in laminin production consistent with a reversion of the malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Under some conditions, caveolin-1 has been shown to suppress growth of specific cell lines in vitro and in vivo (Koleske et al, 1995;Engelman et al, 1997;Suzuki et al, 1998), and some have suggested that caveolin-1 functions as a tumour suppressor gene (Engelman et al, 1998b). The reasons behind this seemingly contradictory evidence remain unclear.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%